2010
DOI: 10.1007/s12311-010-0157-x
|View full text |Cite
|
Sign up to set email alerts
|

The Cerebellum in Children with Spina Bifida and Chiari II Malformation: Quantitative Volumetrics by Region

Abstract: Few volumetric MRI studies of the entire cerebellum have been published; even less quantitative information is available in patients with hindbrain malformations, including the Chiari II malformation which is ubiquitous in patients with spina bifida meningomyelocele (SBM). In the present study, regional volumetric analyses of the cerebellum were conducted in children with SBM/ Chiari II and typically developing (TD) children. Total cerebellar volume was significantly reduced in the SBM group relative to the TD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 52 publications
2
33
0
Order By: Relevance
“…Because of the Chiari II malformation, the cerebellum and its connectivity to other brain regions is impaired in SBM ( Juranek et al, 2010). Hand function also reflects the cerebellar influences on precision and timing of fine motor movements.…”
Section: Dtt Volume and Integrity Of The CCmentioning
confidence: 99%
“…Because of the Chiari II malformation, the cerebellum and its connectivity to other brain regions is impaired in SBM ( Juranek et al, 2010). Hand function also reflects the cerebellar influences on precision and timing of fine motor movements.…”
Section: Dtt Volume and Integrity Of The CCmentioning
confidence: 99%
“…These changes include malformations of the hindbrain and cerebellum that are the hallmarks of spina bifida, along with decreased WM integrity in limbic regions and impaired long-association pathways as measured by diffusion tensor imaging (DTI). 24,25 A small longitudinal study of children having acute hydrocephalus indicated that 7 of 10 cases displayed elevated fractional anisotropy (FA) in the posterior limb of the internal capsule and decreased FA in the genu of the corpus callosum. However, these increases in FA normalized after insertion of a ventriculoperitoneal shunt.…”
mentioning
confidence: 99%
“…However, they found that posterior fossa cerebrospinal fluid (CSF) volume improves and reaches to almost normal values after posterior fossa decompression as compared to normal individuals. In a recent investigation [3], total cerebellar volume was found to be significantly reduced in spina bifida myelomeningocele group as compared to the normal individuals. The results of this investigation coincide with the observations of the group, who proposes posterior fossa decompression in early infancy.…”
mentioning
confidence: 84%